Corneal macular dystrophy. Case Presentation. - Leopoldo Garduño-Vieyra; Bruno Flores Escobar; Isabel De la Fuente Batta (Ukrainian Society of Ophthalmologists, 2022)
Among the stromal corneal dystrophies corneal macular dystrophy is one of the most frequent. It is an autosomal recessive disorder linked to chromosome 16, in which a mutation occurs in the CHST6 gene, causing an alteration in keratan sulfate metabolism. This alteration produces extracellular deposits of glycosaminoglycans between the stromal lamellae of the cornea, as well as in the cytoplasm of the endothelial cells. Clinically, the presence of centrally predominant white-greyish focal stromal corneal opacities is observed in early stages. Symptoms begin between the second and third decade of life and consist of progressive decrease in visual acuity and photophobia. In this work, we present the clinical case of a 56-year-old male patient who came to the clinic due to progressive decrease in visual acuity and photophobia. On physical examination, multiple intrastromal macules, whitish in color, were found by biomicroscopy in both eyes that were accentuated in greater quantity in the central 5 mm of the cornea. According to the findings obtained in the examination, the diagnosis of corneal macular dystrophy is established.